Structured learning environments are required to promote equitable participation. Issue 1 (11th October 2018) - Neill, Connor; Cotner, Sehoya; Driessen, Michelle; Ballen, Cissy J.
Abstract : It is critical that we understand and address features of learning environments that encumber students historically underrepresented in STEM fields. Here we consider social elements of group work that can either support or impede learning. We tracked gender-bias in student–teaching assistant (TA) interactions in 184 small groups across 27 introductory chemistry laboratories in fall 2017. We demonstrate that in some environments male students interacted with TAs disproportionately more than female students. To promote verbal participation of women in introductory chemistry courses, we advocate for improved TA training programs that teach a host of equitable teaching strategies to enhance the climate of the classrooms and consequently, improve learning. Fostering a structured, inclusive classroom environment is the first step towards achieving equity more broadly across STEM.